Predictors of the quality of the relationship between informal caregiver and care recipient in informal caregiving of older people: presentation and evaluation of a new item - Becker, Linda; Grässel, Elmar; Pendergrass, Anna (BMC Psychology, 2024)
Background: An important factor that has not been directly addressed very often in caregiver (CG) counseling to date is the quality of the relationship between the CG and the care recipient (CR). One reason is the lack of availability of a suitable assessment tool that is not strongly influenced by social desirability. Here, we present and evaluate a new item for the assessment of relationship quality (RQ) in the context of informal caregiving of older people. Methods: N = 962 informal caregivers of older people participated. Our item assessed RQ by providing three answer categories (positive, neutral, and negative) that were presented through the use of smiley faces. For evaluation, and to avoid bias due to social desirability, the neutral and negative categories were combined. We calculated a stepwise binary logistic regression. Results: Expected associations with the variables care burden, perceived positive aspects, and care motivation were found (all p values < 0.01). An exploratory analysis revealed that additional predictors of RQ consisted of the CR’s age as well as whether the CR’s diagnosis was dementia, CG’s amount of dysfunctional coping, and whether the CG was caring for more than one CR. Conclusions: We conclude that our item is well-suited for the assessment of RQ in the context of informal caregiving of older people. Because it uses language-free answer categories by means of smiley faces, our item can be applied easily. Bias due to social desirability can be minimized by dichotomization (i.e., combining the negative and neural answer categories). In future research, our tool should be evaluated in other contexts.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Assessment tool; Caregiver burden; Caregiving motivation; Caregiving stress; Geriatric care; Informal caregiving; Positive aspects; Relationship quality; Social desirability